Inhibition of lipopolysaccharide‐induced osteoclast formation and bone resorption in vitro and in vivo by cysteine proteinase inhibitors. Issue 5 (14th February 2017) - Strålberg, Fredrik; Kassem, Ali; Kasprzykowski, Franciszek; Abrahamson, Magnus; Grubb, Anders; Lindholm, Catharina; Lerner, Ulf H.
Abstract : The inhibition of RANKL and LPS‐induced osteoclast formation by cysteine proteinase inhibitors demonstrate the role of cysteineproteinase(s) in physiological and pathological osteoclastogenesis. Abstract : Inflammation‐induced bone destruction is a major treatment target in many inflammatory skeletal diseases. The aim of this study was to investigate if the cysteine proteinase inhibitors cystatin C, fungal cysteine proteinase inhibitor (E‐64), and N ‐benzyloxycarbonyl‐arginyl‐leucyl‐valyl‐glycyl‐diazomethane acetate (Z‐RLVG‐CHN2 ) can inhibit LPS‐induced osteoclast formation. Mouse bone marrow macrophages (BMMs) were isolated and primed with receptor activator of NF‐κB ligand (RANKL) for 24 h, followed by stimulation with LPS, with and without inhibitors. Adult mice were injected locally with LPS and then treated with E‐64 and osteoclast formation assessed by the number of cathepsin K + multinucleated cells. Cystatin C inhibited LPS‐induced osteoclast formation time and concentration dependently (IC50 = 0.3 μM). The effect was associated with decreased mRNA and protein expression of tartrate‐resistant acid phosphatase (TRAP) and cathepsin K and of the osteoclastogenic transcription factors c‐Fos and NFATc1. LPS‐induced osteoclast formation on bone slices was also inhibited by cystatin C, resulting in decreased pit formation and release of bone matrix proteins. Similar data were obtained with E‐64 and Z‐RLVG‐CHN2 . Cystatin C was internalized in BMMs stimulated by LPS but not in unstimulated BMMs. Osteoclast formation induced by LPS was dependent on TNF‐α, and the 3 inhibitors abolished LPS‐induced TNF superfamily 2 (gene encoding TNF‐α; Tnfsf2 ) mRNA expression without affecting Il1b, Il6, or oncostatin M ( Osm ) expression. Formation of osteoclasts in the skull bones after local LPS stimulation was inhibited by E‐64. It is concluded that cysteine proteinase inhibitors effectively inhibit LPS‐induced osteoclast formation in vivo and in vitro by inhibition of TNF‐α expression. The targeting of cysteine proteinases might represent a novel treatment modality for prevention of inflammatory bone loss.